Improving Students' Speaking Skill Through Cooperative Script: A Collaborative Research At The Eight Grade Of SMP N 1 Nguter In 2016/2017 Academic Year - Puji Astuti, Purwanti, Nur Hidayat, M.Pd (2017)
SUMMARY PURWANTI PUJI ASTUTI. A320120257. IMPROVING STUDENTS' SPEAKING SKILL THROUGH COOPERATIVE SCRIPT: A COLLABORATIVE RESEARCH AT THE EIGHT GRADE OF SMP N 1 NGUTER IN 2016/2017 ACADEMIC YEAR. RESEARCH PAPER. ENGLISH DEPARTMENT. SCHOOL OF TEACHER TRAINING AND EDUCATION. MUHAMMADIYAH UNIVERSITY OF SURAKARTA. The objectives of the research are 1) to identify whether cooperative script method can improve students' speaking skill, 2) to describe the strengths and weaknesses of cooperative script method. The type of the research that is used by the researcher is action research. The subject of the research was the eighth grade students of SMP N 1 Nguter. Data of the research are the interview script, lesson plan, and the score of pre-test and post-test. The data sources are event, informants, and document. The researcher analyzed the data using qualitative and quantitative method. The quantitative data was collected from the students' speaking skill scores through test, while qualitative data was obtained from observations and interviews. The result of the research showed that from the implementation of cooperative script at the eighth grade students of SMP N 1 Nguter, the speaking skill of the students is improved significantly. It can be seen from the achievement score of the students also the achievement of Minimum Requirement Score or in Indonesia it is called Kriteria Ketuntasan Minimum (KKM). From the test result, the mean scores increased from cycle to cycle. The mean score of pre-test is 47.4, the mean score of post-test 1 in cycle 1is 65.18, and the mean score of post-test 2 in cycle 2 is 76.59. The implementation of cooperative script is effective to improve the students' speaking skill. Kata Kunci: Cooperative Script, Speaking Skill